2008
DOI: 10.1021/ie8000452
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Decomposition of Hydrogen Peroxide over Pd/SiO2 Catalyst

Abstract: Kinetics of hydrogen peroxide decomposition over Pd/SiO 2 catalyst was investigated as part of a larger project to determine the overall kinetics of hydrogen peroxide formation by Pd/SiO 2 catalyzed direct combination of hydrogen and oxygen. A Pd oxidative/reductive cycle mechanism for the decomposition of H 2 O 2 over Pd/ SiO 2 was proposed. A Rideal-Eley rate expression based on this mechanism was shown to accurately correlate experimental data over a wide range of H 2 O 2 concentration and temperature. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 18 publications
1
46
0
Order By: Relevance
“…This is a prerequisite for safe and long-term operation. Voloshin et al studied in detail the kinetics of direct synthesis of hydrogen peroxide over a Pd catalyst by isolating and separately studying direct synthesis [10] , hydrogenation [9] and decomposition [8] reaction in a packed-bed microchannel. Their work also indicated that the catalyst activity is highly influence by the reaction environment.…”
Section: Page 3 Of 31mentioning
confidence: 99%
See 2 more Smart Citations
“…This is a prerequisite for safe and long-term operation. Voloshin et al studied in detail the kinetics of direct synthesis of hydrogen peroxide over a Pd catalyst by isolating and separately studying direct synthesis [10] , hydrogenation [9] and decomposition [8] reaction in a packed-bed microchannel. Their work also indicated that the catalyst activity is highly influence by the reaction environment.…”
Section: Page 3 Of 31mentioning
confidence: 99%
“…The effect of acid addition on the kinetics of the hydrogen peroxide decomposition over aPd catalyst was studied previously in detail by Voloshin et al [8] . We observed that at a sulfuric acid content of 0.05M and a NaBr content of approximately 10 ppm, the decomposition reaction is completely inhibited.…”
Section: Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…For both catalyst loadings, the amount of peroxide formed is significantly lower for the Pd-based catalyst than for the commercial Pt catalyst at potentials lower than 0.7 V vs. SHE. Both Pt and Pd not only produce H 2 O 2 during oxygen reduction (23,28), but are also active catalysts for hydrogen peroxide decomposition (29)(30)(31)(32). Vetter et al measured decomposition rates with Pt catalysts at various temperatures and determined the first order decomposition rate constant at 20-30 °C in pH 7 solution to be 3.6 x 10 -4 s -1 (29).…”
Section: Ecs Transactionsmentioning
confidence: 99%
“…In addition, Co (II)-monoethanolamine complex immobilized on Dowex-50W resin [39] has been effectively used for the decomposition. Moreover, functional inorganic supports have also been used for immobilization M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 of transition metal catalysts such as silica [40], propylpiperazine-silica matrix [41] and silicasand-goethite slurries [42] applied for this aim.…”
mentioning
confidence: 99%